Preferential Liberalization, Antidumping, and Safeguards: Stumbling Block Evidence from MERCOSUR - P. Bown, Chad (2016)
There is not yet consensus in the trade agreements literature as to whether preferential liberalization leads to more or less multilateral liberalization. However, research thus far has focused mostly on tariff measures of import protection. We develop more comprehensive measures of trade policy that include the temporary trade barrier (TTB) policies of antidumping and safeguards; studies in other contexts have also shown how these policies can erode some of the trade liberalization gains that arise when examining tariffs alone. We examine the experiences of Argentina and Brazil during the formation of the MERCOSUR over 1990-2001, and we find that an exclusive focus on applied tariffs may lead to a mischaracterization of the relationship between preferential liberalization and liberalization toward non-member countries. First, any ‘building block’ evidence that arises by focusing on tariffs during the period in which MERCOSUR was only a free trade area can disappear once we also include changes in import protection that arise through TTBs. Furthermore, there is also evidence of a ‘stumbling block’ effect of preferential tariff liberalization for the period in which MERCOSUR became a customs union, and this result tends to strengthen upon inclusion of TTBs. Finally, we also provide a first empirical examination of whether market power motives can help explain the patterns of changes to import protection that are observed in these settings. Aún no hay un consenso en la literatura sobre acuerdos comerciales con respecto a si la liberalización preferencial conlleva a más o a menos liberalización multilateral. Sin embargo, hasta ahora las investigaciones se han enfocado mayormente en medidas arancelarias de protección a las importaciones. En este estudio desarrollamos medidas de política comercial más completas que incluyen las políticas de barreras temporales al comercio (BTC) de antidumping y salvaguardias; estudios en otros contextos también han mostrado cómo estas políticas pueden erosionar parte de las ganancias de la liberalización comercial que surgen cuando se examinan sólo los aranceles. Examinamos las experiencias de Argentina y Brasil durante la formación del MERCOSUR en 1990-2001, y hallamos que un enfoque exclusivo en aranceles aplicados puede llevar a una caracterización equívoca de la relación entre liberalización preferencial y liberalización hacia países no miembros. Primeramente, cualquier evidencia de “building block” que surge al enfocarse en aranceles durante el periodo en el que MERCOSUR fue sólo un área de libre comercio puede desaparecer cuando también incluimos cambios en la protección a las importaciones que ocurren a través de BTC. Además, hay evidencia de un efecto de “stumbling block” de la liberalización comercial arancelaria para el periodo en el cual MEROCUSR se volvió una unión aduanera, y este resultado tiende a fortalecerse con la inclusión de BTC. Finalmente, también proveemos una primera evaluación empírica sobre si motivos de poder de mercado pueden ayudar a explicar los patrones de los cambios en la protección a las importaciones que se observan en estos escenarios.